Konsep Merdeka Belajar Ditinjau Dari Filsafat Pendidikan Paulo Freire: The concept of freedom to learn in terms of Paulo Freire's educational philosophy - Cardoso1, Norberto G.; Wahini2, Ni Made Prema; Toha, La Ilham (Undiksha, 2024)
Good Education is the goals and aspiration of an independent nation. The role of aducation is one of indicators of the assessment of an advanced nation in producing superior human resources. This research is a philosophical research that discusses the concept of Merdeka Belajar from the perspective of Paulo Freire's philosophy of education. The concept of Merdeka Belajar has become a paradigm in the world of education that emphasizes the independence and freedom of learning of each individual. The concept of Merdeka Belajar has become a hot conversation in the world of education in Indonesia because it makes a new breakthrough in the world of education. The concept of Merdeka Belajar is allegedly a solution to the problem of education in Indonesia. In Indonesia, the learning system still uses a memorization system and bank style. Freire's Philosophy of Education highlights several major problems in the world of education, namely education with the banking system, curriculum design that is still rigid and unsustainable, lack of infrastructure, and teaching methods that are still passive. The learning model makes students not free to be creative in the teaching and learning process. This research is a study that uses qualitative-descriptive research methods, with the data collection technique being a literature study. This research proposes the integration of Merdeka Belajar concept and Freire's liberation education principles, which provide a strong philosophical foundation for the development of an inclusive and liberating education system for each individual. The results of this study are: (1) the importance of increasing students' active participation in learning; (2) Updating the curriculum and education system to be flexible, modern, and essential. (3) the importance of building criticism, dialog, self-reflection, and developing sensitivity to social reality.